Para pemburu masa depan - Surya Burhanuddin; Hendroyono, Tony (Sleman, Yogyakarta : Bentang, 2016)
On Indonesian students in Malaysia's colleges and universities.
In Indonesian.
Keywords: Educational exchanges -- Indonesia; Educational exchanges -- Malaysia; Indonesian students -- Malaysia